TINJAUAN HUKUM ISLAM TERHADAP PERNIKAHAN DINI - Wahyu Safitri (LPPM-IAI BATAM, 2023)
This article focuses on early marriage. Where early marriage in today's life has become a social phenomenon involving marriage occurring at a relatively young age, especially in adolescents or children. In the context of science and health, early marriage has far-reaching consequences and implications. The review aims to analyze the foundations of Islamic law underlying early marriage, examine Islamic legal perspectives on early marriage, and explore the advantages, challenges, and implications associated with early marriage in Islam. This article also tries to make a fundamental point in dealing with this issue. The research method used is a library study involving analysis of primary sources, such as and secondary sources consisting of books, journal articles, fatwa, analysis results suggest that Islamic law provides the basis for early marriage, taking into account certain aspects, This means that although there is no proof of Islamic law to prohibit early marriage, it does not mean that early marriage can be prohibited. And ideally there should be crucial considerations for such early marriage. However, this review also reveals the advantages and challenges related to early marriage in the context of Islamic law. Benefits of early marriage include the fulfillment of sharia, the stability of the family, and the fulfillment of individual physical and emotional needs. However, early marriage challenges include health risks, as well as physical and psychological imbalances that may occur in married couples at an early age. On the other hand, negative effects also cause domestic violence, divorce and childbirth deaths. In conclusion, early marriage in the review of Islamic law is legal marriage. Nevertheless, it is ideal for the state to be present to consider the continuation of early marriage phenomen that occur in this country considering that there are a number of negative effects that will occur from early marriage.